PERANAN PEMBELAJARAN SOSIOLOGI PADA LEMBAGA BIMBINGAN BELAJAR NEUTRON YOGYAKARTA CABANG BANYUMANIK SEMARANG DALAM MENINGKATKAN HASIL BELAJAR MATA PELAJARAN SOSIOLOGI DI SEKOLAH (Solidarity: Journal of Education, Society and Culture, 2013)
Each tutoring institute have different characteristics with their learnings. In subjects belonging to the non exact sciences, like sociology takes appropriate learning strategies to facilitate students in understanding the material. Tutoring institute has specific strategies that are foundational in every learning. This article explains that sociology learning at the Tutoring Institute of Neutron Yogyakarta, Banyumanik Semarang Branch can be seen from the learning components. Several components contribute to improving learning outcomes in schools. This article also shows that the role of the sociology learning in improving learning outcomes of sociology in school, among others 1) to deepen understanding of the material, 2) makes it easy to answer questions, 3) to overcome difficulties, 4) makes it easy to find examples, and 5) motivating students.